2019
DOI: 10.3390/atmos10080459
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulations of Oil Droplet Aerosol Transport in the Marine Atmospheric Boundary Layer

Abstract: In this study, a hybrid large-eddy simulation (LES) model is developed and applied to simulate the transport of oil droplet aerosols in wind over progressive water waves. The LES model employs a hybrid spectral and finite difference method for simulating the wind turbulence and a bounded finite-volume method for modeling the oil aerosol transport. Using a wave-following coordinate system and computational grid, the LES model captures the turbulent flow and oil aerosol fields in the region adjacent to the unste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…They show that the presence of oil slicks and dispersant alter the splashing and aerosol generation processes, and that the number of microdroplets increases both with oil layer thickness and with addition of dispersants. Second, M. Li et al (2019) apply a wave-effect-resolving LES to simulate the transport of oil droplet aerosols by wind over surface waves in the marine atmospheric boundary layer. They show that wind considerably enhances oil droplet suspension and both vertical and lateral spreading, and that the spatial distribution of aerosols exhibits significant streamwise variations.…”
Section: Aerosolization Of Oilmentioning
confidence: 99%
“…They show that the presence of oil slicks and dispersant alter the splashing and aerosol generation processes, and that the number of microdroplets increases both with oil layer thickness and with addition of dispersants. Second, M. Li et al (2019) apply a wave-effect-resolving LES to simulate the transport of oil droplet aerosols by wind over surface waves in the marine atmospheric boundary layer. They show that wind considerably enhances oil droplet suspension and both vertical and lateral spreading, and that the spatial distribution of aerosols exhibits significant streamwise variations.…”
Section: Aerosolization Of Oilmentioning
confidence: 99%
“…M. Li et al (2019) developed a hybrid large-eddy model to simulate the transport of aerosolized oil droplets (2.5, 40, 60, and 100 µm diameter) over progressive water waves. The model employs a hybrid spectral and finite-difference method for simulating wind turbulence, a bounded finite-volume method for modeling aerosolized oil transport, and a wave-following coordinate system and computational grid to capture the flow fields adjacent to the waves.…”
Section: Advancements In Studying Health Risks From Inhaled Spill Toxinsmentioning
confidence: 99%
“…Unlike high-resolution large-eddy simulations (LES; with grid spacing of ;1-100 m) that resolve turbulence (e.g., Momen and Bou-Zeid 2016;Salesky et al 2016;Momen et al 2018;Li et al 2019), NWP models have to entirely parameterize turbulent fluxes due to their larger grid sizes (;1-30 km) that cannot resolve turbulence. Recent observations and LESs have shown that there are significant distinctions between hurricane turbulence and regular atmospheric boundary layer (ABL) turbulence (Zhang et al 2009;Zhang 2010;Zhang et al 2011Zhang et al , 2017Momen et al 2021;Chen 2022).…”
Section: Introductionmentioning
confidence: 99%